2019
DOI: 10.21037/atm.2019.11.70
|View full text |Cite
|
Sign up to set email alerts
|

The genetic contribution of HLA-E*01:03 and HLA-E*01:03-G*01:01 to Posner-Schlossman syndrome in southern Chinese

Abstract: Background: The polymorphisms of classical HLA-Ia and HLA-II loci have been associated with Posner-Schlossman syndrome (PSS) in the southern Chinese population. However, the associations of non-classical HLA-Ib (e.g., HLA-E and HLA-G) loci with PSS have not been reported for in the southern Chinese population. This study aimed to evaluate the associations of the HLA-E and HLA-G loci with PSS in a southern Chinese Han population group. Methods: Ninety-seven unrelated patients with PSS and 90 ethnically matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Hirose et al reported that the HLA-Bw54 and HLA-Bw54-Cw1 haplotype were overrepresented in patients with PSS in a Japanese population (6). In previous studies, we found that the HLA-C*14:02 and HLA-E*01:03 alleles, and the HLA-A*11:01-C*14:02, HLA-B*51:01-C*14:02, and HLA-E*01:03-G*01:04 haplotypes confer susceptibility to PSS in a southern Chinese population (7,8). However, the role of non-HLA genetic variants in PSS still needs to be investigated.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Hirose et al reported that the HLA-Bw54 and HLA-Bw54-Cw1 haplotype were overrepresented in patients with PSS in a Japanese population (6). In previous studies, we found that the HLA-C*14:02 and HLA-E*01:03 alleles, and the HLA-A*11:01-C*14:02, HLA-B*51:01-C*14:02, and HLA-E*01:03-G*01:04 haplotypes confer susceptibility to PSS in a southern Chinese population (7,8). However, the role of non-HLA genetic variants in PSS still needs to be investigated.…”
Section: Introductionmentioning
confidence: 72%
“…The adaptive immune system maintaining normal function needs appropriate balance between the stimulatory and inhibitory signals (9). The positive costimulatory signal involves the peptide-HLA engagement of the T cell receptor, which is associated with PSS (6)(7)(8)(9). The inhibitory signal is caused by the negative immune checkpoints (e.g., CTLA-4 and PD-1) to spare healthy cells and maintain self-tolerance (9).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, many methods were used to partially or full-length sequence the HLA-E gene containing some SNP sites, including PCR-SBT and PCR-SSP [ 19 , 20 ]. Among these, the PCR-SBT method is considered as the gold standard and its results are accurate and comprehensive; it can help discover new SNP sites.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple genetic loci in human leukocyte antigen (HLA) have been identified to be associated with PSS in Japanese and Chinese populations, such as HLA-Ia, HLA-II, HLA-Bw54, HLA-E, and HLA-G. These recent genetic studies have not only helped shed light on the pathogenesis of the disease, but also have suggested that they share common etiologies with other hypertensive uveitic conditions (5)(6)(7)(8). To date, however, no specific gene other than HLA has been found to directly cause PSS.…”
Section: Introductionmentioning
confidence: 99%